DIGITAL DIPLOMACY OF INDONESIA IN REALIZING ITS VISION AS THE ASEAN DIGITAL ECONOMY HUB - Santoso, Rizal Budi; Moenardy, Dwi Fauziansyah; Rizqi Muttaqin (Indonesian Journal of International Relations, 2024)
This research analyzes Indonesia's digital diplomacy to realize Indonesia's vision of strengthening its position as the center of ASEAN's digital economy and encouraging inclusive and sustainable economic growth in the region. Qualitative methods were used in this research by collecting data through a literature study which was then validated using data triangulation techniques. This research shows that developing digital diplomacy is essential in strengthening Indonesia's position as a digital economy leader in the ASEAN region, including building a solid digital infrastructure, increasing access and digital inclusion, and promoting regional collaboration through the ASEAN Smart Cities Network (ASCN). In achieving this goal, Indonesia can encourage digital inclusion, expand its market, and formulate regulations and policies that support the growth of the digital economy and startups.